Cervical pap smear study: a cytohistological correlation in patients of tertiary care centre - Divya Goud, Sanam; Jyothi, Ch.; Divyagna, T.; Soujanya, R. (International Journal of Research in Medical Sciences, 2025)
Background: The second most prevalent disease in Indian women and a leading source of morbidity and death is cervical cancer. The Pap smear is a quick, low-cost and effective screening technique for early detection of benign and malignant cervical lesions. The objectives of this study were to analyze the cytomorphological patterns of cervical smears, ascertain the frequency of abnormalities in epithelial cells and use histopathological correlation to evaluate the Pap test’s diagnostic accuracy. Methods: From January to December of 2022, this retrospective study was carried out in the pathology department of Gandhi Hospital in Telangana. The Bethesda Reporting System for Cervical Cytology, 2014 was used to analyze and classify conventional Pap smears from women ages 20 to 80. Histopathological findings and abnormal epithelial findings were associated and the diagnostic accuracy, sensitivity, specificity and predictive values were computed. Results: Out of 4,848 satisfactory smears analyzed, epithelial cell abnormalities constituted 1.63% of all cases. The most common abnormality was ASCUS, which was followed by LSIL. Approximately two-thirds of abnormal lesions occurred in women over 40 years of age. Cytological findings demonstrated good concordance with histopathological diagnoses, with an overall diagnostic accuracy of 79.68%. Conclusions: A safe, easy, non-invasive and reasonably priced way to identify precancerous and cancerous cervical abnormalities is through Pap smear screening. By enabling early detection and prompt treatment, routine screening in sexually active women can dramatically lower the incidence of cervical cancer.